PERKUATAN GESER BALOK BETON BERTULANG MENGGUNAKAN GFRP (STUDI KASUS: GOR BAROMBONG MAKASSAR) - Aditya, Muhammad Fathur; Saraswati, Ayu (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Shear failure is recognized as a brittle and sudden collapse mode, making it a critical issue that necessitates effective strengthening solutions for reinforced concrete beam structures. The main objective of this study is to evaluate the effectiveness and feasibility of Glass Fiber Reinforced Polymer (GFRP) composite as external reinforcement to address the shear strength deficit in reinforced concrete beams. The case study focuses on the West Tribune beams of GOR Barombong Makassar, which experienced shear failure due to a combination of low material quality, exposure to an aggressive marine environment, and increased capacity demands resulting from the seismic standard update from SRPMM to SRPMK. The research methodology utilized analytical calculations based on the ACI 440.2R-08 guidelines. Analysis results indicate that the existing shear strength of the beams is 424.23 kN, while the required additional strength varies from 21.57 kN to 53.93 kN to meet the design shear strength. Six GFRP U-Wrap strengthening configurations were analyzed, demonstrating the capability to provide additional shear strength ranging from 26.68 kN to 55.31 kN. The application of a specific GFRP configuration at the beam supports successfully increased the total shear capacity by 6.3% to 13.0%, proving that GFRP is an effective and efficient shear strengthening solution, and is superior due to its non-corrosive properties, making it suitable for aggressive environments.